Challenges in IoMT Adoption in Healthcare: Focus on Ethics, Security, and Privacy - Mabina, Alton; Rafifing, Neo; Seropola, Boago; Monageng, Thapelo; Majoo, Pulafela (Universitas Bina Darma, 2024)
This study highlights ethical, security, and privacy barriers to IoMT adoption in developing countries and proposes strategies like regulatory frameworks, data encryption, AI transparency, and professional training to address these challenges. The Internet of Medical Things (IoMT) has the potential to revolutionize healthcare by enabling real-time patient monitoring, enhancing diagnostic accuracy, and supporting personalized treatments. However, significant privacy, security, and ethical challenges hinder its widespread adoption, particularly in underdeveloped nations. This study employs the PRISMA methodology to systematically review existing literature and identify key barriers to IoMT implementation in healthcare systems, with a focus on developing countries. Through a rigorous selection process, 80 studies were included in the analysis, revealing critical challenges such as inadequate data protection frameworks, ethical concerns around artificial intelligence (AI) in decision-making, and risks of patient data exploitation. The findings provide actionable recommendations for policymakers, including the establishment of robust ethical guidelines, implementation of strong security measures, and use of advanced encryption techniques. Addressing these challenges is crucial to fostering the ethical and secure adoption of IoMT, ultimately improving healthcare outcomes globally Key recommendations for IoMT adoption include the implementation of advanced encryption techniques to safeguard patient data, the establishment of clear informed consent protocols, and the development of ethical guidelines to manage AI’s role in medical decision-making, ensuring transparency and patient autonomy.